Mango - Okino-Delgado, C. H.; Prado, D. Z. [UNESP]; Pereira, Milene Stefani [UNESP]; Camargo, Dafne Angela [UNESP]; Koike, Meliane Akemi [UNESP]; Fleuri, Luciana Francisco [UNESP] (Elsevier, 2020)
Mango is one of the most consumed fruits worldwide, and it is still mostly appreciated in the fresh form. However, the consumption of mango processed products has grown due to the rising demand for practical foods, increases in products shelf life and in the awareness of the benefits of fruits on human health. Mango processing leads to an increase in wastes generation since the pulp, the main product, corresponds to approximately half of the fruit mass. The mango processing wastes have a rich composition, which allows the production of several by-products. Mango by-products can be used by the final consumer, as food ingredients, and as substrates for fermentation processes, and incorporated to several industries such as foods, pharmaceuticals, fine chemicals, cosmetics, cleaning products, and personal hygiene products. Therefore they are a promising alternative for more profitable and sustainable systems since they enable the incorporation of new products into traditional processes.
Keywords: antioxidant; mango flour; Mango peel; mango seed; pomace mango